Fuzzy TOPSIS evaluation approach for business process management software acquisition. Issue 3 (3rd July 2017) - Rouhani, Saeed; Zare Ravasan, Ahad
Abstract: At the present time, Business Process Management software (BPMS) implementation is on focus of organizations. To implement a BPMS in a firm successfully, selecting a suitable BPMS is critical. Evaluation and selection of the BPMS software is complex and a time consuming decision-making process. This paper propounds an approach for dealing with such a decision. This approach introduces functional, non-functional and fuzzy evaluation method for BPMS evaluation. The presented BPM lifecycle based approach breaks down BPMS evaluation and selection criteria into two broad categories namely functional and non-functional requirements including totally 48 selection criteria. A facile Fuzzy Technique for Order Preference by Similarity to Ideal Solution (FTOPSIS) is customized for BPMS selection based on identified criteria. The provided approach is applied to a port and maritime organization in order to evaluate and acquire a BPMS and the provided numerical example illustrates the applicability of the approach. The approach can assist practitioners to evaluate BPMSs more effective.